The Influence of Socialization, Education and Perception in Growing The Interest of Makassar City Residents in Investing in Mutual Funds During The Covid-19 Period - Mustari (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the influence of socialization, education and perception in growing the interest of Makassar city residents in investing in mutual funds during the Covid-19 period. This research uses quantitative descriptive methods. The population in this research is the people of Makassar City, both those who have not invested and those who have invested in mutual funds, totaling 30 people from various age groups. In collecting data, researchers used a questionnaire/questionnaire research instrument which was filled out online and then tested for validity and reliability. Data analysis techniques use multiple linear regression analysis, t test, F test, and coefficient of determination. The results of this research state that the sig. 0.000 < 0.05 in the sense that the independent variables (socialization, education, perception) simultaneously have a significant influence on people's investment interest in mutual funds